Nanocracking and metallization doubly defined large-scale 3D plasmonic sub-10 nm-gap arrays as extremely sensitive SERS substrates. Issue 7 (24th January 2018) - Pan, Ruhao; Yang, Yang; Wang, Yujin; Li, Shuang; Liu, Zhe; Su, Yewang; Quan, Baogang; Li, Yunlong; Gu, Changzhi; Li, Junjie
Abstract : Stress-induced cracking and metallization are combined to fabricate controllably large-scale 3D plasmonic sub-10 nm-gap arrays for extremely sensitive SERS detection application. Abstract : Considering the technological difficulties in the existing approaches to form nanoscale gaps, a convenient method to fabricate three-dimensional (3D) sub-10 nm Ag/SiN x gap arrays has been demonstrated in this study, controlled by a combination of stress-induced nanocracking of a SiN x nanobridge and Ag nanofilm deposition. This scalable 3D plasmonic nanogap is specially suspended above a substrate, having a tunable nanogap width and large height-to-width ratio to form a nanocavity underneath. As a surface-enhanced Raman scattering (SERS) substrate, the 3D Ag/SiN x nanogap shows a large Raman enhancement factor of ∼10 8 and extremely high sensitivity for the detection of Rhodamine 6G (R6G) molecules, even down to 10 −16 M, indicating an extraordinary capability for single-molecule detection. Further, we verified that the Fabry–Perot resonance occurred in the deep SiN x nanocavity under the Ag nanogap and contributed prominently to a tremendous enhancement of the local field in the Ag-nanogap zone and hence ultrasensitive SERS detection. This method circumvents the technological limitations to fabricate a sub-10 nm metal nanogap with unique features for wide applications in important scientific and technological areas.